2014
DOI: 10.1108/jrf-04-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

Herding behaviour and volatility in the Athens Stock Exchange

Abstract: Purpose – This study aims to investigate the existence of herding in the Athens Stock Exchange over the 1995-2010 period and examine its effects on market volatility. Design/methodology/approach – Herding is examined over portfolios formed on beta and size of the selected stocks. The detection of herding has been done using the state space model of Hwang and Salmon (2004). Four volatility measures are employed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 62 publications
(81 reference statements)
1
23
1
1
Order By: Relevance
“…For example, herding behavior was found in the UK (Chiang & Zheng, 2010), China (Chiang & Zheng, 2010;Lao & Singh, 2011;Tan et al, 2008), Hong Kong (Chiang & Zheng, 2010;Lam & Qiao, 2015), Germany, France (Chiang & Zheng, 2010), Italy and Greece (Economou et al, 2011;Messis & Zapranis, 2014). In contrast, this type of behavior was not found by some other researchers studying exactly the same markets, i.e., the UK (Galariotis et al, 2015), China (Demirer & Kutan, 2006), Hong Kong (Chang et al, 2000), Germany, France, Italy, and Greece (Mobarek et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, herding behavior was found in the UK (Chiang & Zheng, 2010), China (Chiang & Zheng, 2010;Lao & Singh, 2011;Tan et al, 2008), Hong Kong (Chiang & Zheng, 2010;Lam & Qiao, 2015), Germany, France (Chiang & Zheng, 2010), Italy and Greece (Economou et al, 2011;Messis & Zapranis, 2014). In contrast, this type of behavior was not found by some other researchers studying exactly the same markets, i.e., the UK (Galariotis et al, 2015), China (Demirer & Kutan, 2006), Hong Kong (Chang et al, 2000), Germany, France, Italy, and Greece (Mobarek et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…The researchers assert that herding behavior by market participants exacerbates market volatility and makes market instable. The empirical findings show that the existence of herding can exacerbate return volatility (Blasco et al, 2012;Demirer & Kutan, 2006;Di Guilmi et al, 2014), however, there are also studies proving that herding behavior has positive effect on return volatility (Messis & Zapranis, 2014;Venezia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Phillipas et al, (2013) found herding behaviour in the US Equity Real Investment Trust (REIT) market. Herding behaviour was also observed by Economou et al, (2011) in Greece, Spain and Italy, Messis and Zapranis (2014) in Athens stock market, Caparrelli et al, (2004) in Italy and Indārs et al,(2018) in Moscow, Russia. Similarly, herding behaviours were observed in other markets such as cryptocurrency by Bouri et al, (2018), in Islamic Gulf Cooperation and Council (GCC) by Chaffai and Medhioub (2018) and in lotterytype stock of Chinese market by Gong and Dai (2018).…”
Section: Introductionmentioning
confidence: 63%
“…Dutta et al,(2016) also examined 50 companies in India national stock market for the period 2006 to 2016 compare to Ganesh et al,(2016) were able to observed herding behaviours leading to research conclusion of Indian markets to be rather semi strong efficient rather than being strong. Messis and Zapranis, (2014) during the period between 1995 to 2010 examine herding behaviours in the Athens stock market. Herding behaviours were observed during this period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mulai dari Benua Asia, perilaku herding terjadi di Vietnam (Vo & Phan, 2016, Pakistan (Shah, Shah, & Khan, 2017), India (Bhaduri & Mahapatra, 2013;Ganesh, Gopal, & Thiyagarajan, 2018), Cina (T. C. Chiang, Li, & Tan, 2010;Gong & Dai, 2017;Lan, 2014;Lao & Singh, 2011;Li, Liu, & Park, 2017;Yao, Ma, & He, 2014;Zheng, Li, & Chiang, 2017), Jepang (Cajueiro & Tabak, 2009;Zheng et al, 2017) Kallinterakis, & Komba, 2017). Lalu, Di Benua Eropa perilaku herding juga terjadi di Perancis (Khan, Hassairi, & VIVIANI, 2011;Litimi, 2017), Jerman (Khan et al, 2011), Italia (Khan et al, 2011), Inggris (Khan et al, 2011), Finlandia (Lindhe, 2012), Romania (Pop, 2013), Portugal (Leite, Machado-Santos, & Silva, 2018), Yunani (Messis & Zapranis, 2014), dan Rusia (Indārs, Savin, & Lublóy, 2019). Terakhir, perilaku herding juga terjadi di Benua Australia (Al-Shboul, 2012).…”
Section: Hasil Dan Pembahasanmentioning
confidence: 99%